2016
DOI: 10.1021/jacs.6b06860
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Visible Light-Driven Splitting of Alcohols into Hydrogen and Corresponding Carbonyl Compounds over a Ni-Modified CdS Photocatalyst

Abstract: Splitting of alcohols into hydrogen and corresponding carbonyl compounds has potential applications in hydrogen production and chemical industry. Herein, we report that a heterogeneous photocatalyst (Ni-modified CdS nanoparticles) could efficiently split alcohols into hydrogen and corresponding aldehydes or ketones in a stoichiometric manner under visible light irradiation. Optimized apparent quantum yields of 38%, 46%, and 48% were obtained at 447 nm for dehydrogenation of methanol, ethanol, and 2-propanol, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
234
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(250 citation statements)
references
References 33 publications
(53 reference statements)
4
234
0
3
Order By: Relevance
“…To minimize power consumption, photocatalysis is a promising approach to replace the conventional thermal process by solar energy in which the photogenerated electrons and holes can participate in organic reactions through various mechanisms . Meanwhile, the potential danger of explosion from high‐pressure H 2 can be avoided through catalytic hydrogen transfer in hydrogenation .…”
mentioning
confidence: 99%
“…To minimize power consumption, photocatalysis is a promising approach to replace the conventional thermal process by solar energy in which the photogenerated electrons and holes can participate in organic reactions through various mechanisms . Meanwhile, the potential danger of explosion from high‐pressure H 2 can be avoided through catalytic hydrogen transfer in hydrogenation .…”
mentioning
confidence: 99%
“…The generality of reaction was established by investigating over two‐dozen substituted benzyl alcohols, heterocyclic substituted alcohols, and α‐alkylated benzyl alcohols. Xu and co‐workers also reported a photocatalytic oxidation of alcohols using Ni‐modified CdS nanoparticles as photocatalysts under visible light irradiation . Both aliphatic and aromatic alcohols were converted into corresponding carbonyl compounds with a high selectivity and along with the evolution of hydrogen under mild conditions.…”
Section: Photocatalysis With Qds For Organic Transformationmentioning
confidence: 99%
“…Xu and co-workersa lso reported ap hotocatalytic oxidation of alcohols using Ni-modified CdS nanoparticles as photocatalysts under visible light irradiation. [24] Both aliphatic and aromatic alcohols were converted into corresponding carbonyl compounds with ah igh selectivity and along with the evolution of hydrogen under mild conditions.…”
Section: Photocatalysis With Qds For Organic Transformationmentioning
confidence: 99%
“…Furthermore, the reactions were conducted in different solvents to study its influence on the photocatalytic oxidation of 1a (Table 2). Interestingly,t he solventh ad ag reat effect on the photocatalytic activity of the 4wt% C 60 /g-C 3 N 4 catalyst towards the oxidation of 1a.N or eaction took place in THF ( Table 2, entry 1), and the reactions in ethanol and benzotrifluoride produced low conversionso f2 2.5 and 30.4 %( Ta ble 2, entries 2 and 3), respectively.A cetonitrile is considered to be the best solventf or photocatalytic reactions in some cases, [36,37] and it also produced ah igh conversion of 83.9 %( Ta ble 2, entry 4); however,t he selectivity of methyl phenyl sulfoxide (1b)w as poor.I th as been reported that Pt/BiVO 4 systems exhibit excel- [a] Reactionc onditions: 1a (0.2 mmol), 4wt% C 60 /g-C 3 N 4 (30 mg), solvent (5 mL), oxygenb alloon,r oom temperature, Xe lamp (1 Wcm À2 , l > 400 nm). ChemSusChem 2018ChemSusChem , 11,2444ChemSusChem -2452 www.chemsuschem.org lent performance fort he oxidation of sulfides in water,c ompared with in organic solvents.…”
Section: Photocatalytic Oxidation Of Sulfidesmentioning
confidence: 99%